Liquid Hand Soap Formulation of Java Citronella (Cymbopogon winterianus) Oil Using Surfactant Combination as Foaming Agent - Martihandini, Nooryza; Aminah, Mimin; Aji, Nur (Poltekkes Kemenkes Surakarta, 2024)
Background: Unhygienic hands can cause microorganism infection. Citronella oil contains citronellal, citronellol, and geraniol, which have antibacterial activity. Liquid hand soap removes the dirt and microorganisms; however, it commonly uses sodium lauryl sulphate (SLS) as a foaming agent that may irritate the skin. Lauryl glucoside is a non-ionic, non-irritating surfactant. This study aimed to formulate and characterise liquid hand soaps from citronella oil using a combination of SLS and lauryl glucoside as surfactants. Methods: The research was conducted using an experimental laboratory method. Three liquid hand soap formulas were developed from 15% citronella oil with different weight ratios of SLS and lauryl glucoside: F1 (1:2), F2 (1:1), and F3 (2:1). Then, all liquid hand soaps were evaluated for organoleptic properties, homogeneity, viscosity, pH, and foam height. Then the foam stability test was conducted after the formed foam was left for 5 minutes. Results: The results showed that all liquid hand soaps were homogeneously distributed, clear viscous liquids having a distinctive odour of citronella oil. The liquid hand soap preparations had a viscosity range of 549.7–565.8 cps, a pH in the range of 7.39–7.89, a foam height of 74–85 mm, and a stability foam of 63.52–68.91%. All formulas complied with SNI 2588:2017 criteria for liquid hand soap. Conclusion: This study presented that citronella oil could be formulated into liquid hand soap using a combination of SLS and lauryl glucoside. The optimal formula was F1 with a 1:2 ratio of SLS and lauryl glucoside. F1 had the most stable foam due to the higher concentration of lauryl glucoside, which enhances foam stability.